THE QUALITY OF TOURISM SERVICES IN BUILDING TOURISM LOYALTY - Tri Palupi Robustin (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Situbondo Regency has a very famous beach as one of the favorite tourism destinations in East Java Province namely Pasir Putih Beach. The objective of this study was to examine the partial and simultaneous effect of the quality of tourism services, consisting of 3 components, i.e., attraction, accessibility, and amenities, on tourist loyalty. Here, explanatory study examined the causal relationship between one variable with another variable by hypothesis test. Population is the tourists who had visited Pasir Putih Beach in Situbondo and sample is 80 respondents taken by purposive sampling technique. Multiple linear regression used to analyze research data. The results of the study showed, the quality of tourism services a partial and simultaneous effect on tourist loyalty.